Analisis Yuiridis Tentang Pembatalan Sertifikat Hak Milik Tanah Oleh Hakim Di Pengadilan Negeri Gorontalo (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The aims of this research are: to know and understand the juridical analysis of the cancellation of land certificates by judges in the city of Gorontalo and to know and understand the judge's considerations regarding the cancellation of land certificates from an administrative perspective. The method used in this research is normative legal research obtained through literature study and primary data obtained in the field. This research took place at the Gorontalo City District Court. The results obtained from this research are that land is a requirement to achieve legal certainty and legal protection of land rights. Conditions for achieving legal certainty and legal protection of land rights. Land registration not only functions to protect the owner, but also functions to find out the status of the land plot, who the owner is, what rights they have, how big it is, what it is used for and so on. In this different legal position, the legal assessment by the judge becomes different, where the sale and purchase deed has the position of assessing the law of the agreement and is subject to the terms of the validity of the agreement, and if it is made illegally the sale and purchase deed can be canceled by the district court.